PRAKTIKALITAS PERANGKAT PERCOBAAN PESAWAT SEDERHANA BERBASIS PERALATAN BUDAYA TRADISIONAL SEBAGAI MEDIA PEMBELAJARAN FISIKA SMP - Dessy Mulyani; Fakhruddin Z '; Hendar Sudrajat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to examine the practicalities of product resulting from the research design and validation aircraft simple experiment devices base on equipment of traditional culture that has been done before. Methodology of the research used is reseacrh and development.This research do in SMP Negeri 18 Pekanbaru with the subject of study aircraft simple experiment devices base on equipment of traditional culture, consist of 3 people science teacher and 36 students junior high school. Practicality data a device on an aircraft simple students obtained through an instrument chief practicalities device according to teachers and students. Analysis of the data in this study is descriptive analysis to categorize the average score of practicalities of aircraft simple experiment devices base on equipment of traditional culture. Based on analysis of the research data obtained the average score to a category very good for all the aspects regarded as on the device experiment the tools and students worksheets of rice pounder, wringer coconut milk, repellent birds, inclide plane and pulley . The conclusion of this research aicraft simple experiment devices base on traditional culture practice devices for use as a medium of learning physics in senior junior school.Key word : Practicality, aircraft simple experiment devices base on equipment oftraditional culture.